Phylogeographical studies in disjunct populations of symplocos laurina wall. using cytoplasmic PCR-RFLP approach - Banu, Sofia; Lagu, Meena D.; Gupta, Vidya S. (Tree Genetics & Genomes, 2010)
Genetic variation, haplotype relationships, and potential regions of diversity in Symplocos laurina Wall. (Symplocaceae), a montane tree species from India, have been tested using molecular and biogeographical data to infer phylogeographic patterns. The polymerase chain reaction-restriction fragment length polymorphism technique was used to determine the chloroplast (cp) and mitochondrial (mt) DNA haplotypes of 218 individuals from 12 populations, collected from Northeast India (NEI), which is a part of Indo-Burma biodiversity hotspot, and South India, which includes the Western Ghats (WG), another biodiversity hotspot from India and Eastern Ghats (EG). Nine cpDNA (chlorotypes) and 24 mtDNA haplotypes (mitotypes) were identified; the WG region was identified as the most diverse for chlorotypes and the NEI region for mitotypes. Although a strong population differentiation was observed, phylogeographic structure was found to be absent for both the genomes. The haplotype network revealed the presence of two main lineages: NEI-WG lineage and EG lineage, largely without overlapping distributions. The study tests two hypotheses, namely vicariance and dispersal, to understand the distribution of plants in India. The population structure of S. laurina strongly suggests the persistence of the species in putative refugial areas preglaciation and further establishment of other populations of S. laurina from these refugial populations.
Keywords: Cytoplasmic genome; Genetic diversity; Phylogeography

Understanding the genetic structure of symplocos laurina wall. populations using nuclear gene markers - Banu, Sofia; Bhagwat, Rasika M.; Kadoo, Narendra Y.; Lagu, Meena D.; Gupta, V. S. (Genetica, 2010)
To characterize the genetic diversity of present populations of Symplocos laurina, which grow in the montane forests in India, we analyzed the DNA sequences of a nuclear gene. Using the 881 bp sequence of cytosolic Glyceraldehyde-3-phosphate dehydrogenase gene, we detected 24 haplotypes among 195 individuals sampled from 14 populations. Two dominant haplotypes were distributed over the entire range of this species in India and several private haplotypes were found. Low genetic diversity within population, high differentiation, number of population specific haplotypes and deviation from neutral evolution characterized the present populations of S. laurina. An analysis of molecular variance indicated the presence of geographic structure within the haplotype distribution. The occurrence of S. laurina preglaciation in India is the most parsimonious explanation for the current geographic structure observed. The populations are presumably ancient and might have spread across its extant distribution range in India through a recent range expansion event.
Keywords: GapC; Genetic diversity; Glaciation; Refugium

Evaluation of genetic variability in Symplocos laurina Wall. from two biodiversity hotspots of India - Bhagwat, Rasika M.; Banu, Sofia; Dholakia, Bhushan B.; Kadoo, Narendra Y.; Lagu, Meena D.; Gupta, Vidya S. (Plant Systematics and Evolution, 2014)
Symplocos laurina Wall., an important medicinal tree species, is one of the pioneering plants for establishment of shola forest ecosystem. We analyzed 208 accessions of S. laurina from 13 populations belonging to three ecoregions in India namely, Western Ghats, Eastern Ghats and Northeast India, to comment on the genetic diversity and population structure of the species. Of the 100 inter simple sequence repeat primers screened, eight were selected based on their clear and reproducible polymorphic patterns. These eight ISSR primers produced on an average 1,014 bands from 208 accessions, of which 6.58 % were rare bands, 55.96 % were shared bands and 37.46 % were similar bands. The primers, UBC835 and UBC880, amplified the highest number of polymorphic loci (16), while the primer UBC852 amplified the least number of amplicons (9). The values for total genetic diversity (H-T) and the average heterozygosity (H-S) were 0.3407 and 0.2263, respectively; while the coefficient of genetic differentiation (G(ST)) was 0.3358. Within-population variance was higher (68 %) than among-population variance (17 %), indicating high intra-population genetic diversity. These populations were grouped according to their geographical location in cluster analysis. Mantel test also showed significant positive correlation between genetic and geographical distances. The present study revealed the importance of the Palghat gap in South India in shaping the distribution of genetic diversity in S. laurina.
Keywords: Biodiversity hotspots; Genetic diversity; ISSR; Palghat gap; Symplocos laurina

Analysis of genetic variability in Aquilaria malaccensis from Bramhaputra valley, Assam, India using ISSR markers - Banu, Sofia; Baruah, Darshana; Bhagwat, Rasika M.; Sarkar, Purabi; Bhowmick, Ananya; Kadoo, Narendra Y. (Flora, 2015)